Sorption isotherm, glass transitions and state diagram for freeze-dried plum skin and pulp - Telis, V. R. Nicoletti [UNESP]; Sobral, P. J. Do Amaral; Telis-Romero, J. [UNESP] (SAGE Publications, 2006)
Differential scanning calorimetry (DSC) was used to determine phase transitions of freeze-dried plums. Samples at low and intermediate moisture contents, were conditioned by adsorption at various water activities (0.11≤a w≤0.90) at 25°C, whereas in the high moisture content region (a w>0.90) samples were obtained by direct water addition, with the resulting sorption isotherm being well described by the Guggenheim-Anderson-deBoer (GAB) model. Freeze-dried samples of separated plum skin and pulp were also analysed. At a w≤0.75, two glass transitions were visible, with the glass transition temperature (T g) decreasing with increasing a w due to the water plasticising effect. The first T g was attributed to the matrix formed by sugars and water. The second one, less visible and less plasticised by water, was probably due to macromolecules of the fruit pulp. The Gordon-Taylor model represented satisfactorily the matrix glass transition curve for a w≤0.90. In the higher moisture content range T g remained practically constant around T g′ (-57.5°C). Analysis of the glass transition curve and the sorption isotherm indicated that stability at a temperature of 25°C, would be attained by freeze dried plum at a water activity of 0.04, corresponding to a moisture content of 12.9% (dry basis). © 2006 SAGE Publications.
Keywords: Differential scanning calorimetry; Glass transition; Isotherms; Moisture; Sorption; Plasticising effect; Plum; Sorption isotherm; Fruits; Prunus domestica